Czuj w czas o sobie cny czytelniku Pieśni V Jana Kochanowskiego - Bakuła, Kordian (Dydaktyka Polonistyczna, 2020)
The article concerns the school reading of the Songs V, Eternal Disgrace of J. Kochanowski, which has been present in high school’s and technical school’s textbooks for decades. The critical moment is not understanding certain expressions, such as a „pitiful loot”, „to manage light people”, „we get in”, which leads to a weakening of the understanding of the entire piece. The author draws attention to the insufficient number of footnotes in the textbooks, not always correct, and therefore proposes to increase the linguistic and factual explanations, improve the existing ones, for which he used historical and contemporary dictionaries. He calls for readers’ vigilance, especially important in the case of old novels.